Development of Basic Chemistry E-Module Based on Problem-Based Learning for Chemistry Education Students - Eny Enawaty (Postgraduate, University of Mataram, 2023)
This research was motivated by the lack of educational material on Basic Chemistry with math problems and the use of digital technology. The aim of this study is to create a problem-based learning-based fundamental chemistry (PBL) module for students of chemistry education at Tanjungpura University. Research form is research and development (R&D) with 4 D model. Research process includes: 1) Define, 2) Design, 3) Develop, 4) Dissemination. The sample for this study included second-semester students of Tanjungpura University's chemistry education degree program who had taken basic chemistry courses. The data collection technique used is an indirect communication technique. The data collection tool used a feasibility questionnaire on the physical, media and linguistic aspects, each of which was validated by two validators. Data analysis technique is done by qualitative descriptions. Based on the results of data analysis, the average feasibility of the content aspect reached 95.00% (very feasible criterion), 97.50% of the communication aspect (very feasible criterion) and 95.00% of the language (a very feasible criterion). The Problem-Based Learning-Based Electronic Basic Chemistry (PBL) module is very suitable to use for basic chemistry learning with a feasibility of 95.625% (very doable) and feedback of students have a feasibility level of 78.03% (good), it can be concluded that the basic electronic chemistry module under the problem-solving learning method is very feasible to use in learning